Translating the combination of TGFβ blockade and radiotherapy into clinical development in glioblastoma - Zhang, Mengxian; Lahn, Michael; Huber, Peter E. (OncoImmunology, 2012)
To improve multimodal glioblastoma treatment strategies, it appears useful to integrate a selective inhibitor of the TβR-I kinase, which may be able to potentiate radiation responses by increasing apoptosis and cancer-stem-like cell targeting while blocking DNA damage repair, invasion, mesenchymal transition and angiogenesis.1
Published online: 17 Oct 2012
Gesehen am 30.07.2018